Analisis Penerapan Manajemen Resiko Pembiayaan Pada BMT Istiqomah Unit 2 Tulungagung - Shandy, Moch. Ilham (Universitas Muhammadiyah Ponorogo, 2024)
The aim of this research is to analyze the application of financing risk management or credit risk at BMT Istiqomah Unit 2 Tulungagung. This research method uses descriptive qualitative research. Data collection techniques use observation and interviews. The results of this research show that the important point of the 5C principle at BMT Istiqomah Unit 2 Tulungagung prioritizes character in analyzing financing. However, other principles are also considered important so that all 5C principles are still used at BMT Istiqomah Unit 2 Tulungagung. The results of this research show that in the process of distributing financing, BMT Istiqomah Unit 2 Tulungagung uses the 5C principle to minimize bad credit. BMT Istiqomah Unit 2 Tulungagung is an Islamic financial institution that operates in accordance with sharia savings and loan cooperative regulations which utilizes funds originating from the community in the form of savings, and funds originating from third parties. Then distribute funds to the community through financing.